Effect of Silver nanoparticles on Passive Avoidance learning in Rats - parvin khodarahmi (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: Silver nanoparticles (Ag NPs) have been widely used in many technologies to produce medical devices, food technology and textiles. Silver nanoparticles may be absorbed through the lungs and intestine into circulation and thus may reach such organs as the liver, kidney, spleen, heart and testes and brain. It has been demonstrated that silver nanoparticles may have toxic effects on mammalian cells. There are some alarming reports on the adverse effects of silver nanoparticles on reproduction of experimental animals. Exposure to silver nanoparticles may exert a neurotoxic effect and affect cognitive functions, causing the impairment of short-term and working memory. The purpose of this study was to investigate the possible protective role of Ag NP on the learning and memory of rats.